Plantation Houses of North Florida - Eduardo Robles (Vitruvio: International Journal of Architectural Technology and Sustainability)
The concept of Plantation conjures an image that identifies the North Florida / South Georgia region of the U. S. Leon County attracted many cotton planters from Georgia, Virginia, Maryland, North and South Carolina in the 1820’s to the 1850’s. Up to the beginning of the Civil War, Leon County was the 5th largest producer of cotton counting all counties from Florida and Georgia. The Civil War brought the plantation culture to a standstill.